Social media—Chances and risks for rheumatology Social Media – Chancen und Risiken für die Rheumatologie - Haase, I.; Mucke, J.; Vossen, D.; Knitza, J.; Ruffer, N.; Zeeck, M.; Krusche, M. (Zeitschrift für Rheumatologie, 2022)
The use of social media and social networks has increased significantly in recent years. They are becoming progressively more important as information channels in private and professional contexts. Also, in medicine, social media are already being used in a variety of ways. For example, professional societies and patient interest groups are being increasingly represented in social networks. The broad use and wide audience of these networks offer new opportunities for the field of rheumatology. This review article provides an overview of the characteristics of some major social media platforms and systematically analyses the existing publications in the context of rheumatology. Furthermore, advantages, but also potential risks that may arise due to social media use are being addressed.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Awareness; Crowd sourcing; Data protection; Education; Influencer; Link; Personal rights; Platform; Social networks